2011
DOI: 10.1002/job.739
|View full text |Cite
|
Sign up to set email alerts
|

Leadership of scientists and engineers: A three‐vector model

Abstract: SummaryExisting models have not adequately accounted for the leadership of scientists and engineers engaged in creative work. In this Incubator, we present a model of creative leadership of scientists and engineers and argue that such leaders should possess expertise in three vectors. Implications and directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…Most of the researchers deductively agreed that leadership can stimulate innovative work behaviour [15], [16]. Janssen [17] found evidence that employees responded more innovatively to higher level of job demands when they perceived that their efforts were fairly rewarded by their leader.…”
Section: A Relationship Between Leadership Practices and Innovative mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the researchers deductively agreed that leadership can stimulate innovative work behaviour [15], [16]. Janssen [17] found evidence that employees responded more innovatively to higher level of job demands when they perceived that their efforts were fairly rewarded by their leader.…”
Section: A Relationship Between Leadership Practices and Innovative mentioning
confidence: 99%
“…Several research studies have proven that leadership has positive correlation with organisational climate [16], [22], [23], [31] [10], [15]- [17]. However, in these studies, the author found that the researchers were using different variables of leadership to test the relationship with organisational climate.…”
Section: B Relationship Between Leadership Practices and Organizatiomentioning
confidence: 99%
“…Mumford, Scott, et al () identify idea generation as a singular task and project development, feasibility studies, and market delivery as a group and organizational endeavor. Because of the encompassing nature of the work, Robledo, Peterson, and Mumford () posit a 3‐Vectors Model of Scientific Leadership. The scientist or engineer's role must traverse all three areas involving the individual technical work, the group, and the organization (Robledo et al, ).…”
Section: A Discussion Of the Literaturementioning
confidence: 99%
“…Because of the encompassing nature of the work, Robledo, Peterson, and Mumford () posit a 3‐Vectors Model of Scientific Leadership. The scientist or engineer's role must traverse all three areas involving the individual technical work, the group, and the organization (Robledo et al, ). Different skill sets are needed to navigate a new idea successfully from generation to market delivery.…”
Section: A Discussion Of the Literaturementioning
confidence: 99%
“…Although a number of models of EDM have been proposed-moral reasoning (Rest 1986), personsituation interaction (Trevino 1986), moral development (Kohlberg 1976), intuitionist (Haidt 2001), neurocognitive (Reynolds 2006)-the ethical sensemaking model may be particularly well suited for ethical problems faced in the sciences and engineering due to the nature of the problems faced in these domains. More specifically, scientists and engineers must operate in a sociotechnical context under conditions of tremendous autonomy (Robledo et al 2012). The ethical problems they face typically involve multiple stakeholders with competing concerns and even conflicting professional guidelines (Martinson et al 2005;Werhane 2002), and a number of alternatives could potentially be adopted to solve these problems .…”
Section: Sensemaking Approach To Ethicsmentioning
confidence: 99%